2014
DOI: 10.1021/jf501373a
|View full text |Cite
|
Sign up to set email alerts
|

Monascin Attenuates Oxidative Stress-Mediated Lung Inflammation via Peroxisome Proliferator-Activated Receptor-Gamma (PPAR-γ) and Nuclear Factor-Erythroid 2 Related Factor 2 (Nrf-2) Modulation

Abstract: We speculated that peroxisome proliferator-activated receptor (PPAR)-γ agonists may modulate the oxidative stress pathway to ameliorate the development of airway inflammation. The effect of Monascus-fermented metabolite monascin (MS) and rosiglitazone (Rosi) on oxidative stress-induced lung inflammation was evaluated. Luciferase assay and DNA binding activity assay were used to point out that MS may be a novel PPAR-γ agonist and nuclear factor-erythroid 2 related factor 2 (Nrf-2) activator. We used hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Mitochondria are the major cellular source of ROS (59) and as such are a pharmacological target for ROS production. It is well established that oxidative stress can induce the secretion of inflammatory cytokines and the expression of adhesion molecules and inflammatory mediators in the lung (3,24,27). It has also been shown that maternal smoking can significantly increase oxidative stress in the offspring, including the lung tissue (4).…”
mentioning
confidence: 99%
“…Mitochondria are the major cellular source of ROS (59) and as such are a pharmacological target for ROS production. It is well established that oxidative stress can induce the secretion of inflammatory cytokines and the expression of adhesion molecules and inflammatory mediators in the lung (3,24,27). It has also been shown that maternal smoking can significantly increase oxidative stress in the offspring, including the lung tissue (4).…”
mentioning
confidence: 99%
“…As shown in Figure 5, monascin and ankaflavin influenced the previous work, monascin and ankaflavin improved the ovalbumin-induced BALB/c airway allergic inflammation. 10,16 Monascin also down-regulated the maturation of dendritic cells and Th2 cytokine production. 16 We suggest that monascin and ankaflavin could suppress allergic reaction.…”
Section: ■ Discussionmentioning
confidence: 99%
“…10,16 Monascin also down-regulated the maturation of dendritic cells and Th2 cytokine production. 16 We suggest that monascin and ankaflavin could suppress allergic reaction. To sum up these observations, monascin and ankaflavin may have a relieving effect on type I allergy patients and thus have potential for development into medicine s such as azelastine.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations